Management of a humeral shaft non-union after a Gustilo III C fracture. (December 2015) - Conserva, Vito; Vicenti, Giovanni; Abate, Antonella; Pesce, Vito; Moretti, Biagio
Abstract: A 25-year-old man was admitted to our Department with an open humeral shaft fracture (Gustilo III C); two large wounds were noticed with ulnar artery and median nerve completely dissected. Initial primary treatment included irrigation, debridement and fracture stabilization with a monolateral external fixator followed by vascular and nerve repair and wound closure. At 6 months follow up the patient was able to use his arm without any painful stimuli and a CT scan showed the presence of postero-medial callus formation. Consequently, the external fixator was removed and the patient was discharged to physiotherapy. After 7 months, the patient presented with severe pain and functional impairment with no history of trauma. X rays showed recent re-fracture on a background of oligotrophic nonunion. Revision surgery included debridement of the non-union bone edges, reaming of the medullary canal and insertion of a humeral nail. Six months later osseous healing was noted with complete restoration of shoulder and elbow movement and partial recovery of the median nerve.